Réponses

2013-02-19T14:52:53+01:00
(x+3+4)(x+3-4) -> (x+7)(x-1) X1=-7 X2=1 Donc lexpression sera supérieure ou égale à 0 lorsque x inférieur ou égale à -7 ou supérieur ou égal à 1
2013-02-19T15:18:17+01:00

Bonjour,

 

(x+3)²-4 >= 0

 

(x+3+2)(x+3-2) >= 0

 

A = (x+5)(x+1) >=0

 

x                            -inf         -5           -1             +inf

 

x+5                                 -       0    +            +                    

 

x+1                                 -             -    0       +                

 

(x+5)(x+1)                     +      0    -    0       +                           

 

x <=-5

 

x >= -1

 

a+